Pengembangan LKPD Berbasis HOTS pada Materi Fungsi di Madrasah Aliyah - Salsabila, Isra Risky; Tambunan, Efrida Pima Sari (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to produce a product development of student worksheets (LKPD) based on biology higher order thinking skills (HOTS) in class X fungi that are valid and practical. This study uses the Research and Development (R&D) method with a 4-D development model: the definition stage, the design stage, the development stage, and the dissemination stage. The validation of the worksheets was carried out by material experts and media experts by providing an assessment questionnaire for the feasibility test of the worksheets. The results of the validation of the material experts get a percentage of 72.61% with appropriate criteria with the total validation percentage in the content feasibility aspect of 71.11% with appropriate criteria, then in the presentation feasibility aspect of 73.33% with appropriate criteria, in the learning presentation aspect, it is 80% with eligible criteria and linguistic aspects of 78% with appropriate criteria. The media expert validation gets a percentage of 80% with the validation percentage on the LKPD size indicator getting a percentage of 80%, then the cover design indicator getting a percentage of 80%, and the module content design indicator getting a percentage of 80%. The total number of teacher response assessments as a whole is a percentage of 89.499% with very decent criteria. the results of the trial for students got 86.07% with very decent criteria (very interesting) with aspects of interest and benefits reaching a percentage of 83.54%, material aspects reaching a percentage of 82.57%, and linguistic aspects reaching a percentage of 90.10 %. LKPD is declared feasible and ready to be used as teaching materials in learning.